Study Kuantitatif Deskriptif Kualitas Hidup Ibu Yang Memiliki Anak Cerebral Palsy Di Yayasan Rumah Gadang Cerebral Palsy Padang - Oktavia Rahtu Dwiyani; Nurhastuti Nurhastuti (Jurnal Riset Sosial Humaniora dan Pendidikan, 2023)
This study discusses the quality of life of mothers who have children with cerebral palsy at the Rumah Gadang Cerebral Palsy Padang Foundation. The variable in this study is the quality of life of mothers who have children with cerebral palsy. This study uses a descriptive quantitative research method. The approach taken in this study is a quantitative approach because the data to be obtained from this research is in the form of numbers which will be analyzed using statistics to draw conclusions. The results of the statistical test research were analyzed using the SPSS program with a total sample of 11 people. The results of the research obtained were physical aspects (38.17%), psychological aspects (33.76%), social relations aspects (48.17%), environmental aspects (56.35%). In conclusion, it is proven that the quality of life of mothers who have children with cerebral palsy in Padang starting from the physical, psychological, social relations, and environmental aspects is concluded to have poor quality